2016
DOI: 10.3389/fnins.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Adjacent Oxytocin/Vasopressin Gene Region and Associations with ASD Diagnosis and Other Autism Related Endophenotypes

Abstract: Background: There has been increasing interest in oxytocin (peptide: OT, gene: OXT) as a treatment pathway for neurodevelopmental disorders such as Autism Spectrum Disorder (ASD). Neurodevelopmental disorders affect functional, social, and intellectual abilities. With advances in molecular biology, research has connected multiple gene regions to the clinical presentation of ASD. Studies have also shown that the neuropeptide hormones OT and arginine vasopressin (AVP) influence mammalian social and territorial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…33 In addition, three polymorphisms of OXT (rs6084258, rs11697250, and rs877172) were found to associate with plasma oxytocin levels. 33 Using neuroimaging of 26 ASD children, a tentative association between the oxytocin receptor (OXTR) gene and N-acetylaspartate of the right medial temporal lobe in ASD has been reported 34 ; however, resequencing of the OXTR gene did not confirm any significant association with the three rare non-synonymous variations, that is, rs35062132 (R376G/C), rs151257822 (G334D), and g.8809426G>T (R150S), and ASD. 35 This is contradictory to a previous study that reported a significant association of these single nucleotide polymorphisms (SNP) with ASD and confirmation by functional studies.…”
Section: Oxytocinmentioning
confidence: 99%
See 2 more Smart Citations
“…33 In addition, three polymorphisms of OXT (rs6084258, rs11697250, and rs877172) were found to associate with plasma oxytocin levels. 33 Using neuroimaging of 26 ASD children, a tentative association between the oxytocin receptor (OXTR) gene and N-acetylaspartate of the right medial temporal lobe in ASD has been reported 34 ; however, resequencing of the OXTR gene did not confirm any significant association with the three rare non-synonymous variations, that is, rs35062132 (R376G/C), rs151257822 (G334D), and g.8809426G>T (R150S), and ASD. 35 This is contradictory to a previous study that reported a significant association of these single nucleotide polymorphisms (SNP) with ASD and confirmation by functional studies.…”
Section: Oxytocinmentioning
confidence: 99%
“…Genetic variation in the OXT gene has found to be associated with phenotypic features of ASD that help to identify subgroups within the spectrum. A study of 108 European trios and another sample of 156 trios (207 probands) demonstrated a significant association between OXT rs6084258 and several endophenotypes of ASD . In addition, three polymorphisms of OXT (rs6084258, rs11697250, and rs877172) were found to associate with plasma oxytocin levels .…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, she had isolated herself because of her physical symptoms. Although behavioural effects of AVP have been described [45], evidence that variants in the AVP gene causing FNDI should have any direct effect on behaviour is lacking. It has previously been reported using self-assessment tools that DI affects the quality of life [19].…”
mentioning
confidence: 99%
“…found single nucleotide polymorphisms, such as the C allele of rs4813625, were associated with more internalizing behaviours in children (Francis et al 2016) and adult females (Love et al 2012).…”
Section: Genesmentioning
confidence: 97%